Unintended consequences of the potential phase-out of gamma irradiation - Chou, Jacquelyn W (F1000Res, 2018)
The radioisotope cobalt-60 (Co-60) is important for commercial, medical, and agricultural applications. Its widespread use has meant that Co-60 can be found in less secured facilities, leading to the fear that unauthorized persons could obtain and use it to produce a “dirty bomb”. This potential security concern has led to government calls for phasing-out Co-60 and other radiation sources, despite ongoing safety and security regulations for handling, transport and use of radioactive sealed sources. This paper explores potential implications of phasing out radioisotopic technologies, including unintended safety and cost consequences for healthcare and food in the US and globally. The use of Co-60 for healthcare and agricultural applications is well-documented. Co-60 is used to sterilize single-use medical devices, tissue allografts, and a range of consumer products. Co-60 is used in Gamma Knife treatment of brain tumors in over 70,000 patients annually. Co-60 is also used to preserve food and kill insects and pathogens that cause food-borne illness. Co-60 is effective, reliable, and predictable. Limitations of alternative sterilization technologies include complex equipment, toxicities, incompatibilities with plastic, and physical hazards. Alternative ionizing radiation sources for wide-reaching applications, including e-beam and x-ray radiation, have advantages and drawbacks related to commercial scale capacity, penetrability, complexity and reliability. Identifying acceptable alternatives would require time, costs and lengthy regulatory review. FDA testing requirements and other hurdles would delay replacement of existing technologies and slow medical innovation, even delaying access to life-saving therapies.  A phase-out would raise manufacturing costs, and reduce supply-chain efficiencies, potentially increasing consumer prices, and reducing supply. These consequences are poorly understood and merit additional research. Given Co-60’s importance across medical and non-medical fields, restrictions on Co-60 warrant careful consideration and evaluation before adoption.